QR VERIFICATION OF LABORATORY STUDIES RESULTS - Kadirkulov, K.; Ismailova, А.; Beissegul, A.; Satybaldiyeva, A. (Academic Scientific Journal of Computer Science, 2021)
This article describes the practical using of QR codes [1] verification of laboratory studies results. QR codes have become widely used in all industries as quick identification of information and the implementation of transactional actions, where encrypted URL allows to quickly scanning by using a smartphone camera. Digitalization contributes to the transition to the online environment of healthcare, office workers, education and to receive more data on the spread of diseases, exchange information and quickly receive laboratory results without distortion. The presented solution is a component of the LIS SmartLAB platform [2], which performs complex automation of laboratories of the different profiles, observing all work processes to obtain reliable results by direct interaction with laboratory equipment according to international standards HL7 (Health Level 7 - "Seventh level"), ASTM (American Society for Testing and Materials - "American Society for Testing Materials") and automatic detection of deviations from standard values [3]. In 2019, there was a pilot implementation of QR verification of results based on the laboratory of the Skin and venereal dispensary of the Almaty, the results of which made it possible to introduce QR codes into other profiles of laboratory diagnostics, such as PCR (polymerase chain reaction), genetics, microbiology and clinical diagnostics. Now, due to the pandemic, all laboratory results for the detection of RNA of the COVID-19 virus must contain a QR code to avoid falsification of the results.